Construct validity and reliability of social support assessment instrument to identify football talent among Malaysian male players aged 13 to 14 years old - Ahmad Hashim (Tanjong Malim, 2019)
Construct validity and reliability of social support assessment instrument to identify football talent among Malaysian male players aged 13 to 14 years old by Ahmad Hashim